2011
DOI: 10.1103/physrevlett.106.186104
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Friction on Stepped Surfaces of Ionic Crystals

Abstract: We report on high-resolution friction force microscopy on a stepped NaCl(001) surface in ultrahigh vacuum. The measurements were performed on single cleavage step edges. When blunt tips are used, friction is found to increase while scanning both up and down a step edge. With atomically sharp tips, friction still increases upwards, but it decreases and even changes sign downwards. Our observations extend previous results obtained without resolving atomic features and are associated with the competition between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 19 publications
6
33
1
Order By: Relevance
“…The stick-slip response of the graphene edge when laterally scanning with well-maintained, sharp tips can be qualitatively understood through extension of a recently proposed effective potential under low normal loads in the vicinity of an atomic step, ⁄ ⁄ . 29 In this model is a constant of order an eV, is the effective barrier width at the edge ( 0) which should be on the order of the tip apex radius, and and are constants larger than which represent a slow recovery of the potential. Assuming that such a potential describes the graphene edge, even when it has been flexed, the value of represents the relative position of the tip to the graphene edge.…”
Section: 31mentioning
confidence: 99%
See 1 more Smart Citation
“…The stick-slip response of the graphene edge when laterally scanning with well-maintained, sharp tips can be qualitatively understood through extension of a recently proposed effective potential under low normal loads in the vicinity of an atomic step, ⁄ ⁄ . 29 In this model is a constant of order an eV, is the effective barrier width at the edge ( 0) which should be on the order of the tip apex radius, and and are constants larger than which represent a slow recovery of the potential. Assuming that such a potential describes the graphene edge, even when it has been flexed, the value of represents the relative position of the tip to the graphene edge.…”
Section: 31mentioning
confidence: 99%
“…26 Although it has long been known that there are significant increases in lateral force signals at atomic scale steps, 27,28 the source of these increases has been of ongoing debate. 24,[29][30][31] Elimination of these localized increases, while maintaining the overall atomic-scale surface topography, could have significant implications towards the realization of low-friction micro-and nano-electromechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…These properties can be studied by AFM probe going across the graphene edges. So far, most of the studies have been devoted to increased 25 sliding friction at step edges of graphite [34, 35,36,37,38,39,40,41,42], MoS 2 [37] and NaCl [37,43] due to a Schwoebel-Ehrlich barrier at steps. The lateral force was applied by AFM probes going across graphene edges in order to study bending properties of functionalized graphene islands [44] and few-layer graphene sheets [45], and to investigate elastic properties of graphene [46] as 30 …”
Section: Introductionmentioning
confidence: 99%
“…It has been found that lateral forces change locally when nanoscale tips slide across step edges. [6][7][8][9][10][11] In atomic-scale studies of surface steps, the chemistry and stability of atomic steps are strongly influenced by the environment. For example, atomic steps on ionic crystals become mobile in the presence of water vapor.…”
Section: Introductionmentioning
confidence: 99%